Optimal sizing and location of distributed generation for loss minimization using ant colony optimization - Wan Mohammad Syahir Wan Abdillah (2023)
The application of ant colony optimization to simulate the optimal sizing and location of distributed generation in IEEE 33 bus distribution system is shown in this thesis. By integrating the distributed generation in the distribution networks, there are various benefits that can be obtained. A few of the benefit for installing the distributed generation in the distribution network are reducing the real power losses and voltage profiles can also be improved. These advantages can be successfully achieved when the distributed generation have the optimal size and location in the system. The main objective for this project is to do an improvement of the voltage profiles and the minimization of real power losses. The distributed generation placement strategy to reduce the real power losses and improving the voltage profiles by using the ant colony optimization is also shown in the thesis. To determine whether the distributed generation is optimally located and sized in the system, the simulation data is analyzed, and it is shown that the decreases of real power losses in the distribution system is possible and the voltage profiles can be improved. Power flow analysis is used to calculate the real power losses and the voltage profiles. To complete the power flow analysis in the IEEE 33 bus distributed network, the backward and forward sweep technique is used. The simulation of ant colony optimization using MATLAB software is also explained in the thesis.